EDUCATION MARKETING STRATEGIES IN IMPROVING THE IMAGE OF EDUCATION INSTITUTIONS - Faiqoh Faiqoh (Eduvis : Jurnal Manajemen Pendidikan Islam, 2020)
Competition in education becomes inevitable, many educational institutions are abandoned by customers so that the negative dynamics of some educational institutions. Meanwhile, Islamic educational institutions, especially madrassas, are still overwhelmed by secondclass education institutions with a favorable level under public education institutions. There are still many people who are lacking or even not yet know madrasah. Therefore, many changes have to be made, especially madrasah related to the management pattern. Madrasahs as education service providers need to learn and have a passion for increasing customer satisfaction because education is a circular process that is facing each other and sustainable. The madrasah initiative starts from finding out. In a world full of innovation, competition and expansion, marketing terms need to be redefined. The marketing of educational services in Madrasahs does not necessarily mean commercialization, but prioritizes quality education, and provides excellent service to its stakeholders. Abstrak Persaingan di bidang pendidikan menjadi tidak terelakkan, banyak lembaga pendidikan yang ditinggalkan pelanggan sehingga terjadi dinamika negatif dari beberapa lembaga pendidikan. Sementara itu, institusi pendidikan Islam khususnya madrasah masih terbebani oleh institusi pendidikan kelas dua dengan level yang menguntungkan dibawah institusi pendidikan umum. Masih banyak orang yang kurang atau bahkan belum mengenal madrasah. Oleh karena itu, banyak perubahan yang harus dilakukan, terutama madrasah terkait dengan pola pengelolaannya. Madrasah sebagai penyelenggara jasa pendidikan perlu belajar dan memiliki semangat untuk meningkatkan kepuasan pelanggan karena pendidikan merupakan proses melingkar yang saling berhadapan dan berkelanjutan. Inisiatif madrasah dimulai dari mencari tahu. Dalam dunia yang penuh dengan inovasi, persaingan, dan ekspansi, istilah pemasaran perlu didefinisikan ulang. Pemasaran jasa pendidikan di Madrasah tidak serta merta berarti komersialisasi, tetapi mengutamakan pendidikan yang bermutu, dan memberikan pelayanan prima kepada stakeholders.